Digital Media Innovation for Enhancing Numeracy Literacy in Elementary Schools - Hidayat, Rosidah Aliim; Wijayanto, Zainnur; Sutama, Sutama (Universitas Muhammadiyah Surakarta, 2024)
The increasing use of digital media in education has emphasized the need for effective tools to enhance numeracy skills among primary school students. These tools provide interactive and engaging learning experiences that can significantly boost mathematical understanding. This study aimed to develop and assess the practicality of digital media for improving numeracy skills in fourth-grade students at Elementary School Dukuh in Kulon Progo. Following the Four-D (4D) model—define, design, develop, and disseminate—the research involved both small- and large-scale trials. Classroom teachers and peer reviewers evaluated the media, rating it as highly practical. The effectiveness of the Microsoft Sway-based tool was confirmed by a high N-Gain Score, indicating substantial improvements in learning outcomes. This study contributes to research on digital media in education by showcasing its potential to support numeracy development. The findings suggest that well-designed digital tools can be widely adopted to improve students' mathematical proficiency and engagement